Review of published evidence on knowledge translation capacity, practice and support among researchers and research institutions in low- and middle-income countries - Violet Ibukayo Murunga; Rose Ndakala Oronje; Imelda Bates; Nadia Tagoe; Justin Pulford (BMC, 2020)
Abstract Background Knowledge translation (KT) is a dynamic and iterative process that includes synthesis, dissemination, exchange and ethically sound application of knowledge to yield beneficial outcomes for society. Effective KT requires researchers to play an active role in promoting evidence uptake. This paper presents a systematised review of evidence on low- and middle-income country (LMIC) researchers' KT capacity, practice and interventions for enhancing their KT practice (support) with the aim of identifying gaps and informing future research and interventions. Methods An electronic search for peer-reviewed publications focusing on LMIC researchers' KT capacity, practice and support across all academic fields, authored in English and from the earliest records available to February 2019, was conducted using PubMed and Scopus. Selected studies were appraised using the Mixed Methods Appraisal Tool, data pertaining to publication characteristics and study design extracted, and an a priori thematic analysis of reported research findings completed. Results The search resulted in 334 screened articles, of which 66 met the inclusion criteria. Most (n = 43) of the articles presented original research findings, 22 were commentaries and 1 was a structured review; 47 articles reported on researchers' KT practice, 12 assessed the KT capacity of researchers or academic/research institutions and 9 reported on KT support for researchers. More than half (59%) of the articles focused on sub-Saharan Africa and the majority (91%) on health research. Most of the primary studies used the case study design (41%). The findings suggest that LMIC researchers rarely conduct KT and face a range of barriers at individual and institutional levels that limit their KT practice, including inadequate KT knowledge and skills, particularly for communicating research and interacting with research end-users, insufficient funding, and inadequate institutional guidelines, structures and incentives promoting KT practice. Furthermore, the evidence-base on effective interventions for enhancing LMIC researchers' KT practice is insufficient and largely of weak quality. Conclusions More high-quality research on researchers' KT capacity, practice and effective KT capacity strengthening interventions is needed. Study designs that extend beyond case studies and descriptive studies are recommended, including better designed evaluation studies, e.g. use of realist approaches, pragmatic trials, impact evaluations, implementation research and participatory action research.